2018
DOI: 10.1111/aos.13929
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and some of its components in relation to risk of cataract extraction. A prospective cohort study of men

Abstract: Purpose To evaluate the relationship between metabolic syndrome and some of its components with the incidence of cataract extraction. Methods A population‐based prospective cohort with a total of 45 049 men, aged 45–79 years, from the Cohort of Swedish Men completed in 1997 a self‐administered questionnaire concerning anthropometric measurements and lifestyle factors. The men were followed from 1 January 1998 through 31 December 2012, and the cohort was matched with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In a Swedish cohort of 35,369 women followed up for a mean of 8.2 years, the metabolic syndrome and its components, abdominal adiposity, diabetes, and hypertension were associated with an increased risk for cataract extraction 5 . These associations were subsequently replicated in another cohort study of 45,049 Swedish men 6 . Meta-analyses based on observational studies also found that an elevated BMI 33 , type 2 diabetes 34 and hypertension 35 appeared to increase the risk of senile cataract.…”
Section: Discussionmentioning
confidence: 71%
“…In a Swedish cohort of 35,369 women followed up for a mean of 8.2 years, the metabolic syndrome and its components, abdominal adiposity, diabetes, and hypertension were associated with an increased risk for cataract extraction 5 . These associations were subsequently replicated in another cohort study of 45,049 Swedish men 6 . Meta-analyses based on observational studies also found that an elevated BMI 33 , type 2 diabetes 34 and hypertension 35 appeared to increase the risk of senile cataract.…”
Section: Discussionmentioning
confidence: 71%
“…After excluding duplicate papers, we screened the remaining articles ( n = 3,027) and disqualified any research that failed to fulfill the inclusion requirements ( n = 2,997) ( Supplementary Figure 1 ). After full-text reviews, nine articles were excluded because of being conducted on patients who underwent kidney transplantation or those with chronic diseases ( n = 2) ( 38 , 39 ), having a case–control or cross-sectional design ( 40 42 ), assessing waist circumference, weight or weight changes rather than BMI ( 28 , 43 , 44 ), and reporting incomplete data ( 45 ). Also, we excluded the study of Yuan et al because they genetically predicted BMI ( 46 ).…”
Section: Resultsmentioning
confidence: 99%
“…First, allergic diseases and cataracts share similar risk factors. Allergic diseases are related to individual components of metabolic risk, such as elevated blood pressure, blood glucose, and high cholesterol levels 18,19 , which may partly explain the increased incidence of cataract formation 20,21 . Other factors, including inflammation, clinical severity of AD, oxidative stress, and corticosteroid use, may contribute to cataract formation.…”
Section: Discussionmentioning
confidence: 99%